High-performance porous alumina ceramic rapidly sintered at low temperature and preparation method thereof

Through the low-temperature rapid sintering technology, porous alumina ceramics with high porosity and excellent performance are prepared by combining specific components, which solves the problems of low porosity and high sintering temperature of existing ceramic materials.

CN119504240AActive Publication Date: 2025-02-25苏州芯合半导体材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510070611.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-02-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing porous alumina ceramics have low porosity, single pore structure, unsatisfactory comprehensive performance, and a high sintering temperature during the preparation process.

Method used

The preparation materials include 55-65% nano-alumina powder, 20-30% low-melting point multi-composite salt, 8-12% polymer pore-forming agent and 3-5% intelligent responsive type. Self-propagation initiator is used to induce a self-propagation exothermic reaction at 200-250°C through laser ignition technology, and sintered at 900-1100°C.

Benefits of technology

Porous alumina ceramics with high porosity and rich pore structure have excellent mechanical properties, thermal conductivity and mass transfer properties, while reducing the sintering temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504240A_ABST
    Figure CN119504240A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance porous alumina ceramic rapidly sintered at low temperature and a preparation method thereof. The alumina ceramic is prepared from the following raw materials in percentage by mass: 55-65% of nano alumina powder, 20-30% of low-melting-point multi-element composite salt, 8-12% of a polymer pore-forming agent and 3-5% of an intelligent response type self-propagating initiator. The polymer pore forming agent is prepared from poly (N-isopropylacrylamide), polyacrylic acid and azobenzene modified polyvinyl alcohol; the intelligent response type self-propagating initiator is a shell-core structure composite material formed by coating Al / Ni with PNVCL; the porous alumina ceramic is prepared from the preparation raw materials through low-temperature sintering. The porous alumina ceramic has relatively high porosity and rich pore structures, has relatively excellent mechanical properties, heat-conducting property and mass transfer property, and also has the characteristic of low-temperature rapid sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a low-temperature fast-sintered high-performance porous alumina ceramic and a preparation method thereof. Background Art

[0002] Porous ceramics are a new type of ceramic material with evenly distributed pores, a very large specific surface area, unique physical surface properties, selective permeability to liquid and gas media, and the ability to absorb energy (such as sound waves) or have damping properties, and have high porosity and low volume density. At the same time, since the ceramic material itself has excellent properties such as high temperature resistance, friction resistance, corrosion resistance, high strength, high hardness and high elastic modulus, this makes porous ceramics, a green material, can be widely used in gas or liquid filtration, purification and separation, chemical catalytic carriers, sound absorption and shock absorption, advanced thermal insulation materials, biological implant materials, special wall materials and sensor materials.

[0003] Among the numerous porous ceramic materials, porous alumina ceramics have the advantages of cheap raw materials, good material strength, low manufacturing cost, low thermal conductivity, anti-aging, etc. Porous alumina ceramics refer to ceramic materials with alumina as aggregate, which are formed with a large number of interconnected or closed pores through material forming and high-temperature sintering processes.

[0004] The existing porous alumina ceramics have low porosity, single pore structure, unsatisfactory comprehensive performance, and high sintering temperature during the preparation process. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a high-performance porous alumina ceramic with low-temperature rapid sintering and a preparation method thereof. The porous alumina ceramic has a high porosity and a rich pore structure, and has excellent mechanical properties, thermal conductivity and mass transfer properties, and has the characteristics of low-temperature rapid sintering.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions: A low-temperature fast-sintering high-performance porous alumina ceramic, wherein the raw materials for its preparation include the following components in percentage by mass: 55-65% of nano alumina powder, 20-30% of low-melting-point multi-component composite salt, 8-12% of polymer pore-forming agent and 3-5% of intelligent response type self-propagating initiator; the intelligent response type self-propagating initiator is a shell-core structure composite material of PNVCL coated Al / Ni; the polymer pore-forming agent includes poly (N-isopropylacrylamide), polyacrylic acid and azobenzene-modified polyvinyl alcohol; the porous alumina ceramic is prepared by low-temperature sintering using the raw materials for preparation.

[0007] Furthermore, the particle size of the nano alumina powder is 20-50 nm.

[0008] Furthermore, the low melting point multi-component composite salt is a Li2CO3-Na2CO3-K2CO3-CsCl composite salt.

[0009] Furthermore, the preparation method of the PNVCL coated Al / Ni shell-core structure composite material is: adding vinyl caprolactam monomer, crosslinking agent and initiator to the Al / Ni alloy powder dispersion, and performing polymerization reaction at a certain temperature to obtain the PNVCL coated Al / Ni shell-core structure composite material.

[0010] Furthermore, the raw materials for preparing the high-performance porous alumina ceramics also include 2-4% of multifunctional additives, and the multifunctional additives include graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2.

[0011] Furthermore, the sintering temperature of the high performance porous alumina ceramic is 900-1100°C.

[0012] The present invention also provides a method for preparing a high-performance porous alumina ceramic by low-temperature rapid sintering, comprising the following steps: (1) Mix the raw materials uniformly according to the mass percentage; (2) subjecting the mixture obtained in step (1) to a molding process to form a green body, inducing a self-propagating exothermic reaction of the green body at a temperature of 200-250° C. by laser ignition technology under the protection of an inert gas, and sintering the green body at a temperature of 900-1100° C.; (3) After sintering, the temperature is lowered to obtain high-performance porous alumina ceramics.

[0013] Furthermore, the nano-alumina powder in the preparation raw material is preliminarily subjected to high-temperature surface activation treatment.

[0014] Furthermore, the preparation method of the PNVCL coated Al / Ni shell-core structure composite material in the raw material is: disperse the Al / Ni alloy powder in deionized water, add an appropriate amount of PVP as a dispersant, and ultrasonically disperse it evenly to obtain a dispersion; then add vinyl caprolactam monomer, crosslinker MBA and initiator MPS to the dispersion and stir evenly; transfer the mixed solution into a reactor, introduce nitrogen to deoxygenate, heat to 60~70℃, and carry out polymerization reaction under nitrogen protection for 4~6h; after the reaction, centrifuge, wash and dry the product to obtain the PNVCL coated Al / Ni shell-core structure composite material.

[0015] Furthermore, the low melting point multi-component composite salt in the preparation raw material is preliminarily subjected to vacuum dehydration and then subjected to ball milling for refinement.

[0016] The beneficial effects of the present invention are: (1) The present invention adopts an intelligent response type self-propagating initiator, and the PNVCL shell provides a thermal trigger mechanism. At a relatively low initiation temperature, the PNVCL shell depolymerizes, exposing the Al / Ni core, initiating a self-propagating exothermic reaction, and providing sufficient heat to achieve sintering; thus, the alumina ceramic of the present invention does not require a high sintering temperature, and can initiate an exothermic reaction at only 200-250°C to achieve sintering; (2) The present invention uses Li2CO3-Na2CO3-K2CO3-CsCl composite salt, which has a melting point as low as about 400°C, and can provide a low-temperature liquid phase environment to promote the rapid transmission of the main material. Under the synergistic effect of multiple ions, a complex pore network structure is formed, which optimizes the specific surface area and mass transfer performance of the material; the carbonate therein can also decompose to produce CO2, further increasing the porosity; (3) The present invention adopts a composite system of polymer pore formers, in which poly(N-isopropylacrylamide) provides temperature responsiveness and undergoes phase change during heating to form a macroporous structure; polyacrylic acid is sensitive to pH, and the precise control of the microporous structure is achieved by regulating the local pH value; azobenzene-modified polyvinyl alcohol can undergo configurational changes under the light generated during the sintering process to produce a dynamic pore structure. The three polymers work synergistically to achieve a multi-scale, multi-morphological, and controllable pore structure, further optimizing the specific surface area and mass transfer performance of the material; (4) The present invention also adds multifunctional additives, among which the lamellar structure of graphene oxide can enhance thermal conductivity and mechanical properties, and can also serve as a pore-forming template; boron nitrogen nanotubes provide thermal stability and dielectric properties, and form unique tubular pores; yttrium-stabilized nano ZrO2 can promote phase transformation and toughening at high temperatures, while giving the ceramic material optical functions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a SEM image of the alumina ceramic of Example 3 of the present invention; Figure 2 is a SEM image of the alumina ceramic of Comparative Example 1; Figure 3 This is the SEM image of the alumina ceramic of Comparative Example 2. DETAILED DESCRIPTION

[0018] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The present invention provides a high-performance porous alumina ceramic with low-temperature rapid sintering. The raw materials for preparing the ceramic include the following components in terms of mass percentage: 55-65% of nano alumina powder, 20-30% of low-melting-point multi-component composite salt, 8-12% of polymer pore-forming agent and 3-5% of intelligent response type self-propagating initiator; the low-melting-point multi-component composite salt is Li2CO3-Na2CO3-K2CO3-CsCl composite salt, and the molar ratio is Li2CO3:Na2CO3:K2CO3:CsCl=(40-50 ):(20~35):(15~20):(5~15); the intelligent responsive self-propagating initiator is a shell-core structure composite material of PNVCL coated Al / Ni; the polymer pore-forming agent is a composite system, which includes poly (N-isopropylacrylamide), polyacrylic acid and azobenzene-modified polyvinyl alcohol, and the mass ratio is: poly (N-isopropylacrylamide): polyacrylic acid: azobenzene-modified polyvinyl alcohol = (1.5~2.5): (1~1.5): 1; the porous alumina ceramic is made by low-temperature sintering using the prepared raw materials.

[0020] Wherein, the particle size of the nano alumina powder is 20-50nm.

[0021] The preparation method of the PNVCL coated Al / Ni shell-core structure composite material is as follows: vinyl caprolactam monomer, crosslinking agent and initiator are added to Al / Ni alloy powder dispersion, and polymerization reaction is carried out at a certain temperature to obtain the PNVCL coated Al / Ni shell-core structure composite material.

[0022] In order to further improve the performance of the porous alumina ceramic, the raw materials for preparing the high-performance porous alumina ceramic also include 2-4% of multifunctional additives, wherein the multifunctional additives include graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2, and the mass ratio thereof is: graphene oxide: boron nitrogen nanotubes: yttrium-stabilized nano ZrO2=1:(1.5~2.5):(1.5~2.5).

[0023] The sintering temperature of the high-performance porous alumina ceramic is 900-1100°C.

[0024] The method for preparing the low-temperature fast-sintering high-performance porous alumina ceramic comprises the following steps: (1) Raw material preparation and pretreatment: ① The nano-alumina powder is subjected to high-temperature surface activation treatment, the main purpose of which is to remove surface impurities to increase porosity; the treatment process is: 700~800℃ heat treatment, insulation for 1~4h, heating rate of 5~15℃ / min.

[0025] ② After Li2CO3, Na2CO3, K2CO3 and CsCl are mixed in proportion, vacuum dehydration and ball milling are carried out to form anhydrous salt and make the composite salt particles uniform; the specific treatment process is: vacuum degree 0.085~0.095MPa, temperature 70~80℃, vacuum dehydration time 3~6h; then dry ball milling method is used for ball milling. Among them, the mass of multi-component composite salt: the mass of large grinding ball: the mass of small grinding ball is 1:3:2, the ball milling speed is 40~80rpm, and the ball milling time is 12~18h.

[0026] ③ Preparation of intelligent responsive self-propagating initiator: a) Mechanical alloying treatment of Al / Ni nanocomposite powders The purpose of mechanical alloying Al / Ni nanocomposite powders is to form uniformly dispersed Al / Ni composite powders; The processing equipment adopts ball milling equipment, specifically a planetary ball mill; the ball milling medium is alumina balls; the ball-to-material ratio is 10:1~30:1; the ball milling speed is 200~500rpm; the ball milling time is 5h~8h; the treatment is carried out under an inert atmosphere such as argon to avoid oxidation; the ball milling method adopts intermittent ball milling.

[0027] b) Preparation of PNVCL-coated Al / Ni shell-core composites by in-situ polymerization Al / Ni alloy powder is dispersed in deionized water, and an appropriate amount of PVP (such as polyvinyl pyrrolidone) is added as a dispersant, and ultrasonic dispersion is uniform; vinyl caprolactam monomer (NVCL), crosslinking agent MBA (such as N,N'-methylenebisacrylamide) and initiator MPS (such as ammonium persulfate) are added to the dispersion and stirred evenly; the mixed solution is transferred to a reactor, nitrogen is introduced for deoxygenation, the temperature is raised to 60~70℃, and the polymerization reaction is carried out under nitrogen protection for 4~6h. After the reaction is completed, the product is centrifuged, washed, and dried to obtain a shell-core structure composite material of PNVCL coated Al / Ni.

[0028] (2) Ultrasonic-assisted high shear mixing technology is used to uniformly mix the prepared raw materials according to the mass percentage to achieve nano-scale dispersion of each component; (3) The mixture obtained in step (2) is subjected to a molding process to form a green body, and the green body is sintered at 900-1100° C. by using a laser ignition technology under the protection of an inert gas to induce a self-propagating exothermic reaction at a temperature of 200-250° C.; the self-propagating exothermic reaction lasts for 10-30 seconds; (4) After sintering, the temperature is programmed to cool down and grain growth is controlled to produce high-performance porous alumina ceramics.

[0029] The present invention is further described in detail below through specific examples.

[0030] The preparation method of the intelligent response type self-propagating initiator used in the following examples and comparative examples is: Al / Ni alloy powder was dispersed in deionized water, and an appropriate amount of PVP was added as a dispersant, and ultrasonic dispersion was performed uniformly; vinyl caprolactam monomer (NVCL), crosslinking agent MBA (N,N'-methylenebisacrylamide) and initiator MPS (ammonium persulfate) were added to the dispersion and stirred uniformly, wherein the mass ratio of Al / Ni alloy powder, vinyl caprolactam monomer, crosslinking agent MBA and initiator MPS was 1:4:0.04:0.02; the mixed solution was transferred to a reactor, nitrogen was introduced for deoxygenation, the temperature was raised to 65°C, and the polymerization reaction was carried out under nitrogen protection for 5 hours. After the reaction, the product was centrifuged, washed and dried to obtain a shell-core structure composite material of Al / Ni coated with PNVCL.

[0031] Example 1 A low-temperature fast-sintering high-performance porous alumina ceramic, wherein the raw materials for its preparation include the following components in terms of mass percentage: 55% of nano alumina powder, 28% of low-melting-point multi-component composite salt, 10% of polymer pore-forming agent, 3% of smart responsive self-propagating initiator and 4% of multifunctional additive; the particle size of the nano alumina powder is 30nm; the low-melting-point multi-component composite salt is Li2CO3-Na2CO3-K2CO3-CsCl composite salt, and the molar ratio is Li2CO3:Na2CO3:K2CO3:CsCl=40:30:2 0:10; the intelligent responsive self-propagating initiator is a shell-core structure composite material of PNVCL coated Al / Ni; the polymer pore-forming agent is a composite system, which includes poly (N-isopropylacrylamide), polyacrylic acid and azobenzene-modified polyvinyl alcohol; the mass ratio of poly (N-isopropylacrylamide), polyacrylic acid and azobenzene-modified polyvinyl alcohol is 2:1:1; the multifunctional additive is a compound of graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2; the mass ratio of graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2 is 1:2:2.

[0032] The preparation method of the low-temperature fast-sintering high-performance porous alumina ceramic is as follows: (1) Using ultrasound-assisted high-shear mixing technology, nano-alumina powder that has been subjected to high-temperature surface activation treatment, low-melting-point multi-component composite salt that has been subjected to vacuum dehydration and ball milling, polymer pore-forming agent, intelligent responsive self-propagating initiator, and multifunctional additive are uniformly mixed according to mass percentage; (2) subjecting the mixture obtained in step (1) to a molding process to form a green body, inducing a self-propagating exothermic reaction of the green body at a temperature of 200° C. by laser ignition technology under the protection of an inert gas, and sintering the green body at 900° C.; (3) After sintering, the temperature is programmed to cool down and grain growth is controlled to produce high-performance porous alumina ceramics.

[0033] Example 2 A low-temperature fast-sintering high-performance porous alumina ceramic, the preparation raw materials of which include the following components in mass percentage: 60% of nano alumina powder, 25% of low-melting point multi-component composite salt, 8% of polymer pore-forming agent, 5% of intelligent response type self-propagating initiator and 2% of multifunctional additive; the particle size of the nano alumina powder is 30nm; the low-melting point multi-component composite salt is Li2CO3-Na2CO3-K2CO3-CsCl composite salt, and the compounding ratio thereof is the same as that in Example 1; the intelligent response type self-propagating initiator is a shell-core structure composite material of PNVCL coated Al / Ni; the polymer pore-forming agent is a composite system, which includes poly (N-isopropylacrylamide), polyacrylic acid and azobenzene-modified polyvinyl alcohol, and the compounding ratio thereof is the same as that in Example 1; the multifunctional additive is a compound of graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2, and the compounding ratio thereof is the same as that in Example 1.

[0034] The preparation method of the low-temperature fast-sintering high-performance porous alumina ceramics of Example 2 is the same as that of Example 1.

[0035] Example 3 A low-temperature fast-sintering high-performance porous alumina ceramic, the preparation raw materials of which include the following components in mass percentage: 65% of nano alumina powder, 20% of low-melting point multi-component composite salt, 9% of polymer pore-forming agent, 4% of intelligent response type self-propagating initiator and 2% of multifunctional additive; the particle size of the nano alumina powder is 30nm; the low-melting point multi-component composite salt is Li2CO3-Na2CO3-K2CO3-CsCl composite salt, and the compounding ratio thereof is the same as that in Example 1; the intelligent response type self-propagating initiator is a shell-core structure composite material of PNVCL coated Al / Ni; the polymer pore-forming agent is a composite system, which includes poly (N-isopropylacrylamide), polyacrylic acid and azobenzene-modified polyvinyl alcohol, and the compounding ratio thereof is the same as that in Example 1; the multifunctional additive is a compound of graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2, and the compounding ratio thereof is the same as that in Example 1.

[0036] The preparation method of the low-temperature fast-sintering high-performance porous alumina ceramics of Example 3 is the same as that of Example 1.

[0037] Figure 1 is a SEM image of the alumina ceramic of Example 3 of the present invention; Figure 1 It can be seen that the alumina ceramic of Example 3 is sintered more densely and has a rich porous structure.

[0038] Comparative Example 1 The porous alumina ceramic of Comparative Example 1 is prepared by raw materials comprising the following components in percentage by mass: 65% of nano alumina powder, 20% of low-melting-point multi-component composite salt, 9% of polymer pore-forming agent and 6% of multifunctional additive; the particle size of the nano alumina powder is 30nm; the low-melting-point multi-component composite salt is Li2CO3-Na2CO3-K2CO3-CsCl composite salt, and its compounding ratio is the same as that in Example 1; the multifunctional additive is a compound of graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2, and its compounding ratio is the same as that in Example 1; the polymer pore-forming agent is a composite system, which includes poly (N-isopropylacrylamide), polyacrylic acid and azobenzene-modified polyvinyl alcohol, and its compounding ratio is the same as that in Example 1.

[0039] The preparation method of the porous alumina ceramic of Comparative Example 1 is: (1) using ultrasonic-assisted high-shear mixing technology to uniformly mix nano-alumina powder that has undergone high-temperature surface activation treatment, low-melting-point multi-component composite salt that has undergone vacuum dehydration and ball milling treatment, polymer pore-forming agent, and multifunctional additive according to mass percentage; (2) The mixture obtained in step (1) is molded and sintered to obtain porous alumina ceramics; wherein the sintering temperature is 1350° C. and the sintering time is 3 h.

[0040] The alumina ceramic of Comparative Example 1 has a relatively high sintering temperature; the SEM image of the alumina ceramic is shown in FIG. Figure 2 As shown by Figure 2 It can be seen that the alumina ceramic of Comparative Example 1 is not sintered sufficiently and is not sintered densely.

[0041] Comparative Example 2 The porous alumina ceramic of Comparative Example 2 is prepared from raw materials comprising the following components in mass percentage: 65% of nano alumina powder, 20% of low-melting-point multi-component composite salt, 9% of polymer pore-forming agent, 4% of intelligent responsive self-propagating initiator and 2% of multifunctional additive; the low-melting-point multi-component composite salt is Li2CO3-Na2CO3-K2CO3-CsCl composite salt; the multifunctional additive is a compound of graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2; wherein the particle size of the nano alumina powder is 30 nm; the polymer pore-forming agent is poly (N-isopropylacrylamide).

[0042] The preparation method of the porous alumina ceramic of Comparative Example 2 is: (1) using ultrasonic-assisted high-shear mixing technology to uniformly mix nano-alumina powder that has undergone high-temperature surface activation treatment, low-melting-point multi-component composite salt that has undergone vacuum dehydration and ball milling treatment, polymer pore-forming agent, and multifunctional additive according to mass percentage; (2) subjecting the mixture obtained in step (1) to a molding process to form a green body, inducing a self-propagating exothermic reaction of the green body at a temperature of 200° C. by laser ignition technology under the protection of an inert gas, and sintering the green body at 900° C.; (3) After sintering, the temperature is programmed to cool down to produce high-performance porous alumina ceramics.

[0043] Figure 3 is the SEM image of the alumina ceramic of Comparative Example 2; Figure 3 It can be seen that the porosity of the alumina ceramic in Comparative Example 2 is low and the pore structure is relatively simple.

[0044] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0045] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-performance porous alumina ceramic sintered at low temperature and rapidly, characterized in that: The raw materials for its preparation include the following components in percentage by mass: 55-65% of nano alumina powder, 20-30% of low melting point multi-component composite salt, 8-12% of polymer pore-forming agent and 3-5% of intelligent response type self-propagating initiator; the intelligent response type self-propagating initiator is a shell-core structure composite material of PNVCL coated Al / Ni; the polymer pore-forming agent includes poly N-isopropylacrylamide, polyacrylic acid and azobenzene modified polyvinyl alcohol; the porous alumina ceramic is prepared by low temperature sintering using the raw materials for preparation.

2. The high-performance porous alumina ceramic sintered at low temperature and rapidly according to claim 1, characterized in that: The particle size of the nano alumina powder is 20-50 nm.

3. The low-temperature fast-sintering high-performance porous alumina ceramic according to claim 1, characterized in that: The low melting point multi-component composite salt is Li2CO3-Na2CO3-K2CO3-CsCl composite salt.

4. The low-temperature fast-sintering high-performance porous alumina ceramic according to claim 1, characterized in that: The preparation method of the PNVCL coated Al / Ni shell-core structure composite material is as follows: vinyl caprolactam monomer, crosslinking agent and initiator are added to Al / Ni alloy powder dispersion, and polymerization reaction is carried out at a certain temperature to obtain the PNVCL coated Al / Ni shell-core structure composite material.

5. The low-temperature fast-sintering high-performance porous alumina ceramic according to claim 1, characterized in that: The preparation raw materials also include 2-4% of multifunctional additives, and the multifunctional additives include graphene oxide, boron nitrogen nanotubes and yttrium-stabilized nano ZrO2.

6. The low-temperature fast-sintering high-performance porous alumina ceramic according to claim 1, characterized in that: Its sintering temperature is 900-1100℃.

7. A method for preparing a low-temperature fast-sintering high-performance porous alumina ceramic according to any one of claims 1 to 6, characterized in that: The steps include: (1) Mix the raw materials uniformly according to the mass percentage; (2) subjecting the mixture obtained in step (1) to a molding process to form a green body, inducing a self-propagating exothermic reaction of the green body at a temperature of 200-250° C. by laser ignition technology under the protection of an inert gas, and sintering the green body at a temperature of 900-1100° C.; (3) After sintering, the temperature is lowered to obtain high-performance porous alumina ceramics.

8. The method for preparing the low-temperature fast-sintering high-performance porous alumina ceramic according to claim 7, characterized in that: The nano-alumina powder in the preparation raw material is preliminarily subjected to high-temperature surface activation treatment.

9. The method for preparing a high-performance porous alumina ceramic by low-temperature rapid sintering according to claim 7, characterized in that: The preparation method of the PNVCL coated Al / Ni shell-core structure composite material in the raw material is as follows: Al / Ni alloy powder is dispersed in deionized water, an appropriate amount of PVP is added as a dispersant, and ultrasonic dispersion is performed uniformly to obtain a dispersion; vinyl caprolactam monomer, crosslinking agent MBA and initiator MPS are added to the dispersion and stirred uniformly; the mixed solution is transferred into a reactor, nitrogen is introduced for deoxygenation, the temperature is raised to 60~70°C, and polymerization reaction is carried out under nitrogen protection for 4~6 hours; after the reaction, the product is centrifuged, washed, and dried to obtain the PNVCL coated Al / Ni shell-core structure composite material.

10. The method for preparing the low-temperature fast-sintering high-performance porous alumina ceramic according to claim 7, characterized in that: The low melting point multi-component composite salt in the preparation raw material is preliminarily subjected to vacuum dehydration and then subjected to ball milling for refinement.

Citation Information

Patent Citations

  • Azobenzene polymer film and preparation method and application thereof

    CN112250980A

  • Preparation method of alumina-based porous ceramic material

    CN112624793A

  • Intermetallic compound-carbon nanotube porous composite material and preparation method thereof

    CN113102755A

  • Method for the production of nanostructureable microparticles from fluid media using spray drying

    DE102014011635A1

  • Process for preparing porous support body ceramic by using spheroidizing agent micro powder

    WO2023155929A1